Electronic waste recycling via cryo-milling and nanoparticle beneficiation. Issue 2 (March 2017) - Tiwary, C.S.; Kishore, S.; Vasireddi, R.; Mahapatra, D.R.; Ajayan, P.M.; Chattopadhyay, K.
Abstract : The existing methods for recycling electronic wastes such as the printed circuit boards (PCB), which contains a large number of components and elements, face significant challenges when considering environmentally benign and easily separable disposal targets. We report here a low-temperature ball milling method that breaks down PCBs all the way into nanoscale particles which further enables enhanced separation of its different base constituent materials that are the polymer, oxide, and metal. The recovered materials are easy to be beneficiated as the nanoscale particles produced from milling are mostly single phase particles, compared to the larger particles obtained by other methods that are multiphase mixtures of various constituents. In addition, the recovered nano size particles can be used as starting material for making useful products such as polymer nanocomposites. Our method demonstrates a new and simple nanoparticles beneficiation route for the processing and recycling of electronic wastes into fully separable constituents.